Innovative and cost-effective SesZen-Bio™ with enriched Biotin and improved superior dissolution efficiency - Gadani, Mihir; Badak, Sneha; Upadhyay, Ratna (Creative Pharma Assent, 2024)
Background: Micronutrient deficiencies, including biotin, iron, zinc, and vitamin D, can lead to hair problems such as loss and thinning. This study explores the improvement of SesZen-BioTM, a natural biotin supplement derived from Sesbania grandiflora leaves, to give NI- SesZen-BioTM. Materials: The nature and structure of biotin in SesZen-BioTM were evaluated using C14 analysis and 1H NMR. Further, Sesbania grandiflora was subjected to an improved economic process to give NI-SesZen-BioTM. HPLTC-aided phytochemical profiling was performed for SesZen-BioTM, NI- SesZen-BioTM, and standard S. grandiflora leaf extract. The purity of d-biotin was quantified using HPLC. The dissolution profile of SesZen-BioTM and NI- SesZen-BioTM was tested to determine bioequivalence and compared versus synthetic biotin. Results: NMR and C14 analysis revealed that SesZen-BioTM contained 100% natural d-biotin. The yield for SesZen-BioTM and NI- SesZen-BioTM was found to be 17% and 18%, respectively, and both exhibited phytochemical profiles similar to standard extract. The release rate for SesZen-BioTM was similar till a dose of 500 mg and slowly decreased at higher concentrations (800-100mg). A 350 mg NI- SesZen-BioTM showed bioequivalence to 250 mg and 500 mg for SesZen-BioTM. Percent d-biotin content was 0.5% in SesZen-BioTM and 0.81% in NI- SesZen-BioTM. Conclusion: This new economically driven process yielded NI-SesZen-BioTM, with similar yield, higher biotin (100%natural) content, and similar dissolution profile but at a reduced dosage as compared to SesZen-BioTM and surpassed synthetic biotin with its sustained release format. Thus, NI- SesZen-BioTM is a promising solution for individuals seeking natural supplements for maintaining hair and skin heath.